(untitled) (Revista de História Regional, 2020)
The second half of the nineteenth century brought big changes to the western spaces of the Brazilian State: territories which hadn’t been yet appropriated by the modern and capitalist paradigm became the object of national, commercial and industrial projects. From the perspective of politicians, governments and statesmen, who remotely formulated the guidelines for the occupation of wilderness, nature was seen, above all, as a resource for the economic development of the nation. Vast areas of pantanais would be then, incorporated into Mato Grosso and Brazilian territories through mapping, establishment of transports and communication networks and the institution of modern property rights. Nevertheless, native populations, driven by different logics, rejected the impositions of these new paradigms, trying to keep their dominium over their lands and communities. This paper seeks to analyze transformations and conflicts that occurred in this confrontation between local peoples, capitals and national state. In the immense fields and wetlands of Upper Paraguay River, the Western Bororos would confront the colonialist urge of the Cibils Company which would associated itself to state agents and institutions in order to violently impose specific forms of interaction with nature.